Clinical significance of Candida isolation from dystrophic fingernails. Issue 9 (4th July 2020) - Shemer, Avner; Daniel, Ralph; Lyakhovitsky, Anna; Aghion‐Svirsky, Vered; Kassem, Riad; Rigopoulos, Dimitris; Farhi, Renata; Galili, Eran
Summary: Background: Candida onychomycosis mostly involves fingernails. Yet, in contrast to dermatophytes, Candida isolation from dystrophic fingernails does not prove casualty, as sample contamination and non‐pathogenic Candida growth occur. Characterising treatment outcome of Candida‐positive dystrophic nails is crucial to avoid unnecessary treatment. Objective: To investigate predicators associated with treatment outcome among Candida‐positive dystrophic fingernails. Patients and methods: A retrospective cohort study was carried out among 108 adults with Candida‐positive dystrophic fingernails not cured with adequate systemic anti‐fungal course. Diagnosis was based on a single mycological culture. Patients with treatment failure (n = 85; 78.7% of the cases) were compared to patients with partial response (mild to almost cure; n = 23; 21.3% of the cases) at 9 to 12 months following treatment initiation. Results: Treatment failure was significantly associated with primary onycholysis (odds ratio [OR] 2.8; 95% confidence interval [CI] 1.1‐7.4) and prolonged dystrophy (12.8 vs. 3.7 years in average), compared to partial treatment response. Non‐responders had lower odds to present with distal lateral subungual onychomycosis, compared to partial responders (OR 0.3; 95% CI 0.1‐0.7). Demographic and mycological characteristics, as well as number of nails affected, co‐presence of paronychia, and treatment regime were not found to be associated with treatment response. Conclusion: Candida‐positive primary onycholysis was shown to be non‐responsive to systemic anti‐fungal treatment, suggesting that anti‐fungal treatment is not indicated. For other clinical scenarios, high proportions of treatment non‐response suggest that determining causality of Candida should not be based on a single positive mycological culture.